The influence of an impulsed ion radiation on the sensitivity parameters of integrated circuits to single event effects - Alexander I. Chumakov; Dmitry V. Bobrovsky; Sergey A. Soloviev (Безопасность информационных технологий)
The paper analyzes the features of the experimental evaluation of the cross sections of single event effects (SEE) under the influence of pulsed ion beams. The main reasons that can distort the results of the experiment are multiple ion exposures to the same sensitive area, several single event effects in different elements of integrated circuit (IC) in one exposure pulse, simultaneous effects of dose rate and ionization reaction from a single nuclear particle. All these effects are analyzed and it is shown that when exposed to an ion pulse with dose rate of less than 106 rad(Si)/s, the effects of dose rate  have little effect on the sensitivity of IC to SEE. There may be difficulties when we register single event transient (SET), but due to different reaction parameters, it is possible to separate the effects of dose rate and SET. The effect of ion range on the maximum flux is estimated. It is shown that taking into account the ions range makes it possible to increase the permissible flux several times.